Divergent Paths, Common Destinies: Comparative Sustainability Transitions in Indonesia and Vietnam : Jalan Berbeda, Takdir Bersama: Transisi Keberlanjutan Komparatif di Indonesia dan Vietnam - Rendy Riyanto; Marah Kerma Mardame Manurung; Muhammad Dini Asmara; Hendy Endarwan; Handy Setyawan; Gary Putra Etwanto (OGZ Research & Publishing, 2025)
Objective : This paper presents a policy-oriented comparative analysis of sustainability transitions in Indonesia and Vietnam, focusing on institutional frameworks, governance structures, and policy coherence in the pursuit of sustainable development. Methods : Drawing on primary policy documents, national development plans, and reports from international organizations such as the World Bank, UNDP, and ASEAN, the study adopts a descriptive qualitative methodology to map the interconnections between economic reform, environmental policy, and social inclusion. Research results : The study finds that Indonesia’s decentralized governance fosters participation but suffers from fragmentation, while Vietnam’s centralized model ensures policy coherence yet limits transparency. Their sustainability paths are complementary: Indonesia excels in participatory management, Vietnam in coordinated green industrialization. Integrating both approaches can strengthen ASEAN’s regional sustainability and low-carbon resilience.